Performance modeling from software components. - Wu, Xiuping
When software products are assembled from pre-defined components, performance prediction should be based on the components also. This supports rapid model-building, using previously calibrated sub-models or "performance components", in sync with the construction of the product. The specification of a performance component must be tied closely to the software component specification, but it also includes performance related parameters (describing workload characteristics and demands), and it abstracts the behaviour of the component in various ways (for reasons related to practical factors in performance analysis). A useful set of abstractions and parameters are already defined for layered performance modeling. This work extends them to accommodate software components, using a new XML-based language called Component-Based Modeling Language (CBML). With CBML, compatible components can be inserted into slots provided in a hierarchical component specification based on the UML component model.
Keywords: Design; Languages; Performance; CBML; LQN; Generative programming; Layered queue model; Performance prediction; Software component; Software performance; Submodel